Crimson Peak [videorecording (DVD)] - Toro, Guillermo del, 1964-; Wasikowska, Mia, 1989-; Chastain, Jessica, 1977-; Hiddleston, Tom (Universal Studios Home Entertainment, 2016)
When her heart is stolen by a seductive stranger, a young woman is swept away to a house atop a mountain of blood-red clay; a place filled with secrets that will haunt her forever. Between desire and darkness, between mystery and madness, lies the truth.